Levels of urea and water on the bromatological composition of oat (Avena sativa L) hay - Mina E., Marcelino (2018)
The objective of the study was to determine the bromatological composition of the ammonification of oats hay subjected to four levels of urea and three of water. A completely randomized design was used with four repetitions in a 4x3 factorial scheme. The levels of urea (2, 4, 6%, based on dry matter) and water (20, 30, 40%) added were evaluated. The processed oats were stored in PVC microsilos of 10x60 cm for 60 days. At the opening of the silos, samples were collected to determine DM, CP, mineral matter (MM), NDF and ADF, plus hemicellulose by the difference between the latter components. The DM decreased linearly when using the water levels with 2, 4 and 6% urea. The average CP content increased cubically with the addition of urea (14.52%) in relation to urea-free silage (6.70%) and decreased with water levels (11.89 vs. 9.92%). There was no effect of the urea or water levels on the contents of NDF and ADF. The NDF of the ammonified oats with the levels of urea in combination with 20% of water showed a negative linear effect (58.01 to 47.86% of NDF). This same behavior was observed for hemicellulose (19.10 to 14.74%). The MM was quadratically influenced by the urea levels, estimating a maximum value of 8.13% for the 5.11% level of urea. The ammonification with urea altered the bromatological composition of the oats hay improving its nutritional value.